Assessment of the authenticity of horse chestnut (Aesculus hippocastanum L.) flowers by scanning electron microscopy - A. D. Dunilin; O. V. Trineeva (Разработка и регистрация лекарственных средств)
Introduction. Horse chestnut (Aesculus hippocastanum L.) is a plant widely used in official and folk medicine in many countries. Pharmacopoeia raw materials in the Russian Federation are only horse chestnut seeds. Flowers, due to the fraction of phenolic derivatives and triterpene saponins contained in them, are a promising medicinal plant raw material, presumably having a venotonizing and membrane-protective effect. To obtain medicinal herbal preparations based on horse chestnut flowers, it is required to have regulatory documentation containing a list of quality indicators, including a description of the signs of its authenticity (morphology and anatomy). Scanning electron microscopy is one of the advanced methods that have recently been increasingly used in medicine and pharmacognostic analysis. Unlike light microscopy, the method provides a three-dimensional spatial representation of diagnostically significant signs of medicinal plant raw materials.Aim. The aim of the study was to study the morphology of the surface of horse chestnut flowers by scanning electron microscopy.Materials and methods. The object of the study was dried whole flowers of horse chestnut (Aesculus hippocastanum L.), collected in the Voronezh region in 2023 at the beginning of flowering. The pieces of flowers were pre-sprayed with silicon on an automatic spraying unit Q150R ES (Quorum Technologies Ltd., Great Britain). Micrographs were obtained using the JSM-6510LV electron microscope (JEOL Ltd., Japan).Results and discussion. The micrographs obtained during the analysis showed diagnostically significant features of the flower structure: the epidermal cells of the corolla petals are polygonal, irregularly shaped, some elongated with sinuous folds. Pollen grains can be collected in cluster-like clusters, located separately or found singly. The surface of the corolla petal is covered with numerous often twisting hairs having a rough-warped structure and a cone-shaped base with a clearly defined attachment point. The surface of the staminate filaments is striated, with longitudinal folds with single unicellular hairs. The anther has a folded shape, its surface is lined with scaly epidermal cells with rough and thickened walls. The surface of the calyx, including the pedicel, is also densely pubescent with numerous trichomes.Conclusion. The scanning electron microscopy method was used for the first time to study the morphological and anatomical features of horse chestnut flowers. The structure of the main diagnostically significant structures of this LRS has been clarified. The morphology of the epidermis surface of the petals of the corolla and calyx, trichomes, pollen filaments, anthers and pollen grains of flowers has been determined. It has been established that carbon and oxygen are the predominant elements of the raw materials.